A systematic approach to cytological evaluation of central nervous system tumours - Panth, R (Journal of Pathology of Nepal, 2011)
Smear cytology has been accepted as a suitable alternative to frozen section in intraoperative consultation of central nervous system tumours. Intraoperative smears from neurosurgical specimens permit rapid and accurate diagnosis. Grading of primary tumours may not be always possible on intraoperative smears, but their division into low or high-grade lesions is highly reliable and reproducible if due attention is paid to certain parameters like nuclear atypia, mitotic figures and necrosis. A systematic approach leads to a workable preliminary diagnosis, assures adequate tissue sampling for histological processing and guides the management team to explain the prognosis to the patient party and plan optimal treatment even before the final histological diagnosis is available. Keywords: Intraoperative consultation; Smear cytology; Central nervous system neoplasm DOI: http://dx.doi.org/10.3126/jpn.v1i2.5409 JPN 2011; 1(2): 136-141